Neural anatomy of echinoid early juveniles and comparison of nervous system organization in echinoderms. Issue 6 (29th September 2020) - Formery, Laurent; Orange, François; Formery, Antoine; Yaguchi, Shunsuke; Lowe, Christopher J.; Schubert, Michael; Croce, Jenifer C.
Abstract: The echinoderms are a phylum of marine deuterostomes characterized by the pentaradial (five fold) symmetry of their adult bodies. Due to this unusual body plan, adult echinoderms have long been excluded from comparative analyses aimed at understanding the origin and evolution of deuterostome nervous systems. Here, we investigated the neural anatomy of early juveniles of representatives of three of the five echinoderm classes: the echinoid Paracentrotus lividus, the asteroid Patiria miniata, and the holothuroid Parastichopus parvimensis . Using whole mount immunohistochemistry and confocal microscopy, we found that the nervous system of echinoid early juveniles is composed of three main structures: a basiepidermal nerve plexus, five radial nerve cords connected by a circumoral nerve ring, and peripheral nerves innervating the appendages. Our whole mount preparations further allowed us to obtain thorough descriptions of these structures and of several innervation patterns, in particular at the level of the appendages. Detailed comparisons of the echinoid juvenile nervous system with those of asteroid and holothuroid juveniles moreover supported a general conservation of the main neural structures in all three species, including at the level of the appendages. Our results support the previously proposed hypotheses for the existence of two neural units in echinoderms: one consisting of the basiepidermal nerve plexus to process sensory stimuli locally and one composed of the radial nerve cords and the peripheral nerves constituting a centralized control system. This study provides the basis for more in‐depth comparisons of the echinoderm adult nervous system with those of other animals, in particular hemichordates and chordates, to address the long‐standing controversies about deuterostome nervous system evolution. Abstract : Whole mount immunohistochemistry and confocal microscopy were used on juveniles of three echinoderm species to characterize their neuroanatomy. Detailed comparisons confirmed the conservation, among the three species, of a similar general neuroanatomical organization and revealed equivalent innervation patterns at the level of the appendages (i.e., the podia and the spines).